2009
DOI: 10.1016/j.ijadhadh.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Rate effects for mixed-mode fracture of plastically-deforming, adhesively-bonded structures

Abstract: Mixed-mode fracture of an adhesively-bonded structure made from a commercial adhesive and a dual-phase steel has been studied under different rates. Since mixedmode fracture occurs along the interface between the steel and adhesive, the cohesiveparameters for the interface were required. The mode-II interfacial properties were deduced in earlier work. In this paper the mode-I interfacial toughness and the mode-I interfacial strength were determined at different rates. The mode-I interfacial strength was not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Rate-dependent CZMs have been used extensively to model the fracture of ratedependent materials in general [e.g. [19][20][21][22][23][24][25][26][27][28][29].However, only a few authors have reported the use of rate-dependent CZMs to study the fracture of adhesive joints [15,[30][31][32][33][34][35]. For example, to capture the rate-dependency of failure in adhesive bonds of the double cantilever-beam test specimen, Xuet.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rate-dependent CZMs have been used extensively to model the fracture of ratedependent materials in general [e.g. [19][20][21][22][23][24][25][26][27][28][29].However, only a few authors have reported the use of rate-dependent CZMs to study the fracture of adhesive joints [15,[30][31][32][33][34][35]. For example, to capture the rate-dependency of failure in adhesive bonds of the double cantilever-beam test specimen, Xuet.…”
Section: Introductionmentioning
confidence: 99%
“…In both [15] and [35] the cohesive strength was assumed to be equal to the ultimate tensile strength of the adhesive, and its variation with rate was extracted from experimental stressstrain curves obtained at different rates. Sun et al [32][33][34] reported that the mode I properties of the adhesive were almost rate-independent, until the crack velocity increased such that a transition to a brittle fracture occurred. At this transient, the mode I fracture energy dropped almost by a factor of four (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu and Y. Wei adhesives for joints [14,18]. The cohesive parameters utilized in the models were obtained from special tests.…”
mentioning
confidence: 99%
“…The cohesive parameters utilized in the models were obtained from special tests. For example, the cohesive parameters of mode-I fracture were determined from double cantilever beam (DCB) tests [14,18,19]. Although in some numerical analyses of the SLJ, the adopted parameters of the mixed-mode CZ models were taken from related experimental measurements.…”
mentioning
confidence: 99%